Tradeoff Theory and Leverage Dynamics of High-Frequency Debt Issuers. (14th July 2020) - Eckbo, B Espen; Kisser, Michael
Abstract: We test whether high-frequency net-debt issuers (HFIs)—public industrial companies with relatively low issuance costs and high debt-financing benefits—manage leverage toward long-run targets. Our answer is they do not: (1) the leverage–profitability correlation is negative even in quarters with leverage rebalancing; (2) the speed-of-adjustment to target leverage deviations is no higher for HFIs than for low-frequency net-debt issuers; and (3) under-leveraged HFIs do not speed up rebalancing activity in significant investment periods. Thus, even in the subset of firms most likely to follow dynamic trade-off theory, the theory does not appear to hold.